Photoinduced Enhancement of Chemical Shift Sensitivity to Local Vibrations - Ana Martínez Gutiérrez; Oliver Alexander; Pablo Estévez Alonso; Lorenzo Paoloni; Terry Mullins; Andre Al-Haddad; Thomas M. Baumann; Rebecca Boll; Christoph Bostedt; Simon Dold; Alberto De Fanis; Gianluca Geloni; et al. (Journal of the American Chemical Society, 2026)
Abstract The advent of novel free-electron laser sources enabling time-resolved X-ray photoelectron spectroscopy (tr-XPS) provides a unique opportunity to monitor local chemical environments in real time by measuring sub-eV shifts in core-electron binding energies. These shifts reflect the interplay between electronic excitation and nuclear motion, an interplay that remains largely unexplored. In our combined theoretical and experimental study of fluoropyridine (C5H4FN), we investigate this link by monitoring the evolving chemical environment at the N and F atomic sites as the photoexcited S1 state relaxes to the ground state via a conical intersection. We find that the F site responds primarily to vibrational relaxation, showing minimal sensitivity to the electronic excited state. In contrast, excitation to S1 induces a measurable energy shift at the N site and significantly enhances its sensitivity to local vibrations within the ring. This behavior arises from a photoinduced redistribution of charge, which also increases the Coulomb interaction between the 1s electron at the N atom and the atomic partial charge at an adjacent C atom. This insight opens new avenues for exploring ultrafast dynamics and conical intersection pathways in more complex systems, from photostable DNA bases to light-harvesting materials.